Analisis Pajak Penghasilan Bagi Wajib Pajak Badan Usaha Kecil- Menengah Di Indonesia - Inasius, Fany (Binus Business Review, 2012)
Income Tax on Small and Medium Enterprises (SMEs) has been amended in the Tax Law number 36 of 2008 concerning Income tax (the latest Income Tax Act). In the the latest Income Tax Act, tax rate for small and medium business entity with gross circulation up by 4.8 billion rupiahs receives 50% tariff cuts out of the normal rate. This implies a reduction in rates for small and medium enterprises since 2009 compared to rates based onthe previous Income Tax Act (the old Income Tax Act). However, in the calculation of income tax based on the principle of justice, the old Income Tax Act provides a sense of fairness as the basis of taxation based on profit compared to the latest Income Tax Act which based on sale revenues. This study focuses on a comparison of the tax on SMEs corporation by the latest Income Tax Act and the old Income Tax Act. From the research conducted using comparative research method, descriptive, and document analysis, it shows that there is a decrease in tax rates based on the latest Income Tax Act, but the principle of justice in the taxation of SMEs is still less than the old Income Tax Act.